Antibacterial activity of silver nanoparticles immobilized in zinc oxide-eugenol cement against Enterococcus Faecalis: an in vitro study - Juan Camilo Duque-Aristizábal; Liza María Isaza-Areiza; Diego Tobón-Calle; Martha Elena Londoño-López (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the aim of this study is to evaluate the antimicrobial capacity of silver nanoparticles immobilized in a zinc oxide-eugenol (ZOE) cement against Enterococcus faecalis for potential use in endodontic treatments. Method: experimental in vitro study, performing synthesis of silver nanoparticles (AgNPs) and UV-visible spectroscopy to confirm presence of AgNPs in the prepared solutions. The ZOE mixture was standardized, producing the integrated AgNPs/ZOE material. Scanning electron microscopy (SEM) and Fourier-Transform Infrared Spectroscopy (FTIR) were used to characterize the integrated material; a KirbyBauer assay was finally run to measure the inhibition halos produced by the compound-microorganism interaction. Results: the UV-visible spectroscopy showed presence of AgNPs in the created solution; both SEM and FTIR show that the AgNPs are integrated into the ZOE system, not altering their properties when performed under conditions like those found in the mouth. The Kirby-Bauer assay shows that all samples had inhibition halos. The AgNPs in guava extract had statistically significant differences with the halos of the other samples (p < 0.05). Conclusions: the obtained AgNPs show bactericidal activity against Enterococcus faecalis, as a statistically significant difference was found between the AgNPs suspended in guava extract and the other groups; this will be the starting point for future research